Surface modification of nanofibrous matrices via layer-by-layer functionalized silk assembly for mitigating the foreign body reaction. (May 2018) - Qian, Yuna; Li, Linhao; Song, Yang; Dong, Lili; Chen, Peixing; Li, Xiaoming; Cai, Kaiyong; Germershaus, Oliver; Yang, Li; Fan, Yubo
Abstract: The inherent hydrophobicity and large surface area of electrospun synthetic polymeric scaffolds often cause non-specific protein adsorption, thereby influencing macrophage functions and eventually leading to fibrosis at the tissue-scaffold interface. This work reports fabrication of silk fibroin (SF)-functionalized electrospun polycaprolactone (PCL) fibers by single-component layer-by-layer assembly and decorate the SF with heparin disaccharide (HD), resulting in the non-covalent binding of interleukin-4 (IL-4) with the capacity to modulate macrophage polarization. A modified SF derivative was obtained by diazonium coupling and then covalently bonded with HD via click chemistry to eventually bind IL-4 efficiently and maintain its bioactivity. In vitro studies showed that IL-4 surface-functionalized nanofibrous scaffolds promoted polarization to M2 macrophages in the short-term. Importantly, in a murine subcutaneous implantation model, we found that promoting transient shifts in macrophage polarization at early stage can significantly inhibit the extent of the late foreign body reactions. Furthermore, the results of a transcriptomic profiling showed that MARK, PI3K, JNK and NF-κB signaling pathways played an important role in regulating the macrophage phenotypes in the SF/HD/IL-4-functionalized fibers. Our results suggest that such a strategy offers a new approach for utilizing biological agent surface functionalization to modulate the foreign body reaction to nanofibrous scaffolds.